2003
DOI: 10.5326/0390076
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Renal Nephroblastoma in an Adult Dog

Abstract: An 8-year-old Labrador retriever was diagnosed with a unilateral malignant nephroblastoma and hypertrophic osteopathy. The histopathologically malignant tumor was confined to the renal capsule, but the sarcomatous component was anaplastic, resulting in its classification as a Stage I tumor with unfavorable histopathology. The dog was treated with unilateral nephrectomy, vincristine, and doxorubicin. This dog has remained disease free for >25 months. Reported treatments of renal nephroblastoma in the dog have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…22 This finding corroborates the previous reports of nephroblastomas in dogs up to 8 years of age. 4,17,23 As in previous reports, presenting complaints and clinical signs were nonspecific and included polyuria/ polydipsia, vomiting, and behavior changes. 4 It has been previously reported that an abdominal mass could be palpated in as many as 43% of cases of renal tumors.…”
Section: Discussionmentioning
confidence: 58%
“…22 This finding corroborates the previous reports of nephroblastomas in dogs up to 8 years of age. 4,17,23 As in previous reports, presenting complaints and clinical signs were nonspecific and included polyuria/ polydipsia, vomiting, and behavior changes. 4 It has been previously reported that an abdominal mass could be palpated in as many as 43% of cases of renal tumors.…”
Section: Discussionmentioning
confidence: 58%
“…However, polycythemia has been reported infrequently, and is now recognized as part of paraneoplastic syndromes [6,8,9,11,16]. Other paraneoplastic syndromes of canine renal neoplasia include fever, hypercalcemia, marked neutrophilia, and HO [9,11,14,15].…”
mentioning
confidence: 99%
“…The treatment for HO is to resolve the underlying primary disease and to symptomatically treat any pain and discomfort or other clinical signs [1,5,7,14]. Usually, the proliferated bone change will regress in 2 to 5 weeks after elimination of the underlying cause [5,7,14,15].…”
mentioning
confidence: 99%
“…There are around 20 reported cases of renal nephroblastoma in the veterinary literature (table 5). More recent reports recently had increased survival times, compared with those previously reported (>19,3 >254 and >30 months5). Treatment has varied between cases from nephrectomy alone to nephrectomy with adjunctive chemotherapy (table 5).…”
Section: Discussionmentioning
confidence: 72%